Environmental Legal Frameworks and Practices for Attaining Sustainable Development Goals in Nigeria and Saudi Arabia - Amuda, Yusuff Jelili; Parveen, Rehana (Journal of Posthumanism, 2025)
Environmental conservation, ecological system and climate resilience are core aspects for achieving sustainable development goals (SDGs) in various countries including Nigeria and Saudi Arabia. However, there is less focus of attention for an in-depth and comparative analysis of legal frameworks on environmental conservations and practices towards strengthening mechanisms for achieving sustainable development goals (SDG) in Nigeria and Saudi Arabia. This paper therefore tries to investigate specific environmental legal frameworks and practices that would enhance SDGs in both countries. Content analysis (CA) was part of qualitative research was used on secondary data. Hence, various databases, library resources, and Google Scholar were used to explore relevant scholarly studies. Visualization of Similarities (VOS) was employed to identify the themes through the employment of a search strategy. The results demonstrated that both Nigeria and Saudi Arabia have specific environmental legal frameworks such as Environmental Impact Assessment Act, Harmful Waste Act, and the Climate Change Act which are meant for environmental conservation and climate change resilience. However, various initiatives regarding sustainable development goals (SDGs), laws regulating environmental protection and management transparent legal and regulatory framework and integrating indigenous practices with modern legal frameworks are highlighted to be strengthened in both countries. It is therefore suggested that stakeholders should partake actively in the efficiency and compliance of legal frameworks on environmental laws and regulations in improving environmental conservation, ecology and climate change in order to achieve overall SDGs in Nigeria and Saudi Arabia.